2023
DOI: 10.1002/jor.25677
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic loading induces anabolic gene expression in ACLs in a load‐dependent and sex‐specific manner

Lauren Paschall,
Sabrina Carrozzi,
Erdem Tabdanov
et al.

Abstract: Anterior cruciate ligament (ACL) injuries are historically thought to be a result of a single acute overload or traumatic event. However, recent studies suggest that ACL failure may be a consequence of fatigue damage. Additionally, the remodeling response of ACLs to fatigue loading is unknown. Therefore, the objective of this study was to investigate the remodeling response of ACLs to cyclic loading. Furthermore, given that women have an increased rate of ACL rupture, we investigated whether this remodeling re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…It is well established mechanical cues are critical for tissue development in vivo [1,5,21,22] and drive maturation of engineered tissues in vitro [18,[23][24][25][26][27][28][29][30][31]. In particular, intermittent cyclic loading at or below 5% strain is well established to improve fibril alignment, fibril diameter, and collagen production in engineered tendons and ligaments [1,5,17,[21][22][23][24][25][26][27][28][29][30][31]47]; however the effect at the fiber and fascicle length-scale is largely unknown [1,19,23,48,49]. In this study we found that intermittent cyclic loading accelerates and improves hierarchical collagen organization at the fibril, fiber, and fascicle length-scale (Fig 3-4).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established mechanical cues are critical for tissue development in vivo [1,5,21,22] and drive maturation of engineered tissues in vitro [18,[23][24][25][26][27][28][29][30][31]. In particular, intermittent cyclic loading at or below 5% strain is well established to improve fibril alignment, fibril diameter, and collagen production in engineered tendons and ligaments [1,5,17,[21][22][23][24][25][26][27][28][29][30][31]47]; however the effect at the fiber and fascicle length-scale is largely unknown [1,19,23,48,49]. In this study we found that intermittent cyclic loading accelerates and improves hierarchical collagen organization at the fibril, fiber, and fascicle length-scale (Fig 3-4).…”
Section: Discussionmentioning
confidence: 99%
“…Following harvest, 12 autografts and 12 allografts were prepared for mechanical testing under sterile conditions following a previously published protocol 36 . Briefly, all surrounding tissues were removed, and the femur and tibia were cut down into bone blocks to grip the sample during mechanical loading.…”
Section: Mechanical Loadingmentioning
confidence: 99%
“…The 2 MPa stress level was chosen since it is representative of physiological in situ ACL loading and since preliminary testing found that it was the maximum stress that the reconstructions could sustain for 8 h of cyclic loading. 36…”
Section: Mechanical Loadingmentioning
confidence: 99%
See 2 more Smart Citations